Pengaruh Influencer Marketing dan Parasocial Relationship terhadap Keputusan Pembelian pada Produk Noera Collagen Drink - Sabilla Putri Anantia; Ahmad Johan; Muhamad Hidayat (Journal of Management and Creative Business, 2026)
The rapid growth of social media has transformed marketing communication practices, encouraging companies to utilize influencers as an effective digital marketing strategy to influence consumer behavior. In addition to influencer credibility and attractiveness, the emotional bond established between audiences and influencers, known as a parasocial relationship, may also affect consumers’ purchasing decisions. This study aims to examine the influence of influencer marketing and parasocial relationship on the purchasing decisions of Noera Collagen Drink consumers. A quantitative research method with descriptive and verificative approaches was employed. Data were collected through an online questionnaire distributed to 100 respondents who had been exposed to Noera Collagen Drink promotions through social media influencers. The data were analyzed using validity and reliability tests, descriptive analysis, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination analysis with the assistance of SPSS version 29. The findings indicate that influencer marketing was categorized as good with an average score of 4.14, parasocial relationship was categorized as good with an average score of 3.90, and purchasing decisions were categorized as very good with an average score of 4.21. The hypothesis testing results reveal that both influencer marketing and parasocial relationship have positive and significant effects on purchasing decisions, both partially and simultaneously. These findings imply that influencer credibility and emotional attachment between influencers and audiences play important roles in encouraging consumer purchasing behavior in the digital marketing environment.